Performance of Bambara groundnut (Vigna subterranea L. Verdc.) with rice husk biochar and Christmas Island Rock Phosphate application - Mukhtar Musa; Ajit Singh (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Biochar application could be a sustainable way to enhance the nitrogen fixation in Bambara groundnut and other legumes. The research was conducted to study the effect of rice husk biochar and the Christmas Island Rock Phosphate application on the performance of Bambara groundnut in the study area. Method Two levels of rice husk biochar (0 and10 t/ha) and four levels of Christmas Island Rock Phosphate (0, 20, 40 and 60 kg P2O5/ha) were factorial combined to make a total of eight treatment combinations which were laid out in a randomized complete block design (RCBD) with three replicates. Data were collected on nitrogen content and fixation of the crop. Results Application of rice husk biochar increased the total mean of nitrogen content and N fixed by the crop from 120.0 and 90.9 kg/ha to 147.6 and 114.1 kg/ha, respectively. However, the effect of rock phosphate application on the nitrogen content and fixation of the crop was not observed. Conclusion Rice husk biochar application at10 t/ha alone was sufficient for nitrogen content and fixation of the crop. This implies that farmers in the study area can apply rice husk biochar at10 t/ha to enhance the performance of the crop.